We Were the People : Voices from East Germany's Revolutionary Autumn of 1989 - Philipsen, Dirk, 1959- (Book collections on Project MUSE., 1993)
On the night of November 9, 1989, an electrified world watched as the Berlin Wall came down. Communism was dead, the Cold War was over, and freedom was on the rise-or so it seemed. We Were the People tells the story behind this momentous event. In an extraordinary series of interviews, the key actors in the drama that transformed East Germany speak for themselves, describing what they did, what happened and why, and what it has meant to them. The result is a powerful firsthand account of a rare historical moment, one that reverberates far beyond the toppled wall that once divided Germany and.